Perceived barriers related to testing, management and treatment of HCV infection among physicians prescribing opioid agonist therapy: The C‐SCOPE Study. Issue 9 (11th June 2019) - Litwin, Alain H.; Drolet, Martine; Nwankwo, Chizoba; Torrens, Martha; Kastelic, Andrej; Walcher, Stephan; Somaini, Lorenzo; Mulvihill, Emily; Ertl, Jochen; Grebely, Jason
Abstract: The aim of this analysis was to evaluate perceived barriers related to HCV testing, management and treatment among physicians practicing in clinics offering opioid agonist treatment (OAT). C‐SCOPE was a study consisting of a self‐administered survey among physicians practicing at clinics providing OAT in Australia, Canada, Europe and the United States between April and May 2017. A 5‐point Likert scale (1 = not a barrier, 3 = moderate barrier, 5 = extreme barrier) was used to measure responses to perceived barriers for HCV testing, evaluation and treatment across the domains of the health system, clinic and patient. Among the 203 physicians enrolled (40% USA, 45% Europe, 14% Australia/Canada), 21% were addiction medicine specialists, 29% psychiatrists and 69% were metro/urban. OAT physicians in this study reported poor access to on‐site venepuncture (35%), point‐of‐care HCV testing (16%), and noninvasive liver disease assessment (25%). Only 30% of OAT physicians reported personally treating HCV infection. Major perceived health system barriers to HCV management included the lack of funding for noninvasive liver disease testing, long wait times to see an HCV specialist, lack of funding for new HCV therapies, and reimbursement restrictions based on drug/alcohol use. Major perceived clinic barriers included the lack of peer support programmes and/or HCV case managers to facilitate linkage to care, the need to refer people off‐site for noninvasive liver disease staging, the lack of support for on‐site phlebotomy and the lack of on‐site delivery of HCV therapy. This study highlights several important modifiable barriers to enhance HCV testing, evaluation and treatment among PWID attending OAT clinics.